The presence of religion in the Latin American public space. Notes for a debate: La presencia de la religión en el espacio público latinoamericano. Apuntes para la discusión - Esquivel, Juan (Social compass, 2018)
Religion in the public space constitutes a structuring issue of the contemporary debates of the social sciences of religion. This article mobilizes part of that literature, circumscribing it to the Latin American context. In that attempt, we work in two dimensions. First, we present how, from the historical and political configurations of our region in the debate, problems and questions about the public space are addressed distant from those commonly encountered when the empirical reference corresponds to the United States-Europe map. The aim is to explore the regional particularities for an effort to theoretically and methodologically strengthen the analysis of this topic. The second dimension contemplated in the text is the presentation of concrete empirical situations in which religion in public space is condensed as a controversy, that mobilize and is mobilized by different actors: politicians, religious, academics, media. These two dimensions go through the thematic issue that follows this article.